Forecasting future blood supply and demand in Iceland : a nationwide population-based study - Joniada Dega 1998- (2021)
An important resource of healthcare systems is blood transfusions, and it is crucial to maintain a safe and adequate supply of blood such that timely access is guaranteed. Studies have shown that a concerning risk that might disrupt the balance of blood demand and supply, especially in the years ahead, is the demographic changes since both blood transfusion and donation patterns vary by age, among other factors. However, very little data are available on the medium-, and long-term trends of blood transfusions and blood donations. In that regard, this study aimed to estimate the long-term effect of the changing demography on future blood supply and demand at the national level in Iceland. Based on blood donation data from 2016-2019, a statistical model is created to forecast potential blood supply and demand in Iceland for the next 40 years. Data is obtained from two primary sources to establish the model parameters. Data on the country's composition and population trends are gathered from Statistics Iceland's official website. Statistics on blood donations and transfusions are collected from the Icelandic Blood Bank. One of the key assumptions is that per capita blood supply and demand would remain stable over time. According to the main findings, the supply of whole blood units will increase steadily from 2016 to the upcoming years, peaking in 2050 and then declining again. Demand for red blood cells will outstrip supply starting in 2028. Throughout the prediction era, there is an upward trend in demand for red blood cells. This thesis emphasizes the importance of ongoing monitoring of blood donation and transfusion patterns to take appropriate steps to avoid blood shortages in Iceland. More efforts should be made to increase the recruitment of female blood donors in Iceland since they continue to be significantly underrepresented. Keywords: Blood supply Blood demand Demographic changes Forecast Iceland Mikilvægt úrræði í læknisfræðilegri meðferð er notkun blóðs og blóðhluta í meðhöndlun ýmissa sjúkdóma og ...